Protocol for development and validation of a context-appropriate tool for assessing organisational readiness for change in primary health clinics in South Africa - Brooke-Sumner, C.; Sorsdahl, K.; Lombard, C.; Petersen-Williams, P.; Myers-Franchi, Bronwyn (BMJ PUBLISHING GROUP, 2018)
Introduction: A large treatment gap for common mental disorders (such as depression) exists in South Africa. Comorbidity with other chronic diseases, including HIV and diseases of lifestyle, is an increasing public health concern globally. Currently, primary health facilities as points of care for those with chronic disease provide limited services for common mental disorders. Assessing organisational readiness for change (ORC) towards adopting health innovations (such as mental health services) using contextually appropriate measures is needed to facilitate implementation of these services. This study aims to investigate the validity of the Texas Christian University Organisational Readiness for Change (TCU-ORC) scale in the South African context. Subsequently, we will develop a shortened version of this scale. This study is nested within Project MIND, a multiyear randomised controlled trial that is testing two different approaches for integrating counselling for common mental disorders into chronic disease care. Although the modified, contextually appropriate ORC measure resulting from the proposed study will be developed in the context of integrating mental health into primary healthcare services, the potential for the tool to be generalised to further understanding barriers to any change being implemented in primary care settings is high.